Highly efficient ratiometric nanothermometers based on colloidal carbon quantum dots. Issue 20 (12th April 2021) - Han, Yi; Liu, Yanran; Zhao, Haiguang; Vomiero, Alberto; Li, Ronggui
Abstract : Optical nanothermometers have attracted much attention due to their non-contact and precise measurement with high spatial resolution at the micro- and nanoscales. Abstract : Optical nanothermometers have attracted much attention due to their non-contact and precise measurement with high spatial resolution at the micro- and nanoscales. They can be applied in various fields such as micro-opto-electronics, photonics, and biomedical thermal and pH sensing, while most thermal sensors reported so far contain heavy metals or have low sensitivity. Herein, we demonstrate a highly sensitive ratiometric thermal sensor based on colloidal C-dots. C-dots exhibit dual emission originating from the band gap emission and surface-dominant emission, which show a different temperature-dependent photoluminescence (PL) response. Among different surface-functionalized C-dots, C-dots@OH exhibit an absolute thermal sensitivity of −0.082 °C −1, which is the highest among various types of ratiometric thermosensors, making it a very promising candidate for high-sensitivity, self-calibrated nanoscale thermometry. As a proof-of-concept, C-dots@OH were employed to monitor the intracellular temperature (32–42 °C), showing a clear trend for temperature variation in a single cell, indicating that C-dots could offer a powerful tool for a potential precise measurement of the intracellular temperature. They could also be used as thermal sensors for nano-electronic and optoelectronic devices.